Characteristic of critical thinking test instrument and analysis students’ ability using Rasch model - Siti Saffanah Apriliani; Duden Saepuzaman; Irma Rahma Suwarma (Universitas PGRI Kanjuruhan Malang, 2026)
This study aims to analyze the characteristics of the instrument and students' critical thinking skills on the topic of work and energy using Rasch Model. The analysis conducted includes instrument quality, instrument characteristics as indicated by person-item fit to Rasch Model, and the distribution of students' critical thinking skills. The results of the critical thinking skills test of 82 students were analyzed using Winsteps software version 3.73. The results show that the instrument used is reliable and valid, meeting the criteria for good values for both persons and items. The instrument quality analysis shows that items and persons fit Rasch Model. The Wright Map shows the pattern of students' ability distribution and the difficulty level of items, which align with the analysis of students' abilities categorized as very high, high, low, and very low, and item difficulty levels categorized as very difficult, difficult, easy, and very easy. Item Q9 is the most difficult item, and Q6 is the easiest item. The pattern of students' responses to items is shown in the Scalogram, where there are persons who provide anomalous response patterns. Overall, the instrument used has good quality for measuring students' critical thinking skills and emphasizes the importance of having a range of question difficulties.